췌장주위농양으로 오인된 십이지장게실 1예 - 김선영; 김진남; 권선옥; 차인혜; 류수형; 김유선; 문정섭 (The Korean journal of medicine, 2013)
십이지장은 소화기관에서 대장 다음으로 게실이 호발하는 기관이다. 대부분의 십이지장게실은 무증상이지만 이전의 많은 연구에서 담도석, 췌장염과의 연관성이 제기되고 있다. 또한 십이지장 게실이 팽대부주위종양, 췌장낭종으로 오인된 예가 보고되었다. 저자들은 췌장주위농양으로 오인된 십이지장게실 증례를 경험하여 문헌고찰과 함께 이를 보고하고자 한다. 65세 여자가 상복부통증을 주소로 내원하였다. 병력청취, 신체 검사, 복부전산화단층촬영을 시행하여 급성췌장염으로 진단하였다. 입원치료 중 지속적인 발열로 추적복부전산화단층촬영 검사를 재시행하여 새롭게 발생한 다발성췌장주위농양을 확인하였다. 대부분의 농양은 경피적농양배액술로 호전되었으나 췌장의 구부주위 농양은 크기가 감소하지 않았다. 대장내시경을 이용하여 십이지장 제3부까지 관찰하고 십이지장조영술을 실시하여 구부주위 농양으로 의심하여 경피적배액술을 시행한 병변이 십이지장의 제3부에 위치한 십이지장 게실임을 확인하였다. 향후 임상경과와 맞지 않은 췌장주위농양이 췌장구부에서 의심될 때 십이지장 게실을 감별 질환에 포함해야 한다. The duodenum is the second most common site, after the colon, of diverticuli in the alimentary tract. Although most patients with duodenal diverticuli are asymptomatic, previous studies have demonstrated a possible association between duodenal diverticuli and choledocholithiasis and pancreatitis. In addition, duodenal diverticuli mimicking periampullary tumors and cystic neoplasms of the pancreas have been reported. We report a case of a duodenal diverticulum that mimicked a peripancreatic abscess. A 65-year-old woman was admitted for epigastric pain and vomiting. Abdominal CT confirmed the diagnosis of acute pancreatitis. Follow-up abdominal CT performed for a sustained fever revealed several newly developed peripancreatic abscesses. Most of the abscesses were drained percutaneously, but those around the uncinate process seldom respond to treatment. This patient was confirmed to have a duodenal diverticulum by endoscopy and duodenography. Duodenal diverticuli must be considered in a differential diagnosis of peripancreatic abscesses. KCI Citation Count: 2